Conventional and synthetic asset securitizations in the EU: an analysis of sovereign credit default swap spreads as a tool for measuring convergence to EU - Özbakan, Tuğrul (My University, 2009)
Bu çalışmanın ilk amacı belirli bir alacaklar havuzunun nakit akış performansına dayalı yapılandırılmış bir varlık fonlama tekniği olan menkul kıymetleştirmenin AB ile yakınsama sürecine girmiş Doğu Avrupa ülkelerinin borçlanmasında kullanılmasını analiz etmektir. Tezin ampirik kısmında AB yakınsamasının bu ülkelerin kredi iflas takas aralıklarının üzerindeki etkileri ölçülmektedir. Kredi iflas takası, bir nevi kredi türev enstrümanı olup ağırlıklı olarak sentetik menkul kıymetleştirmelerde kullanılmaktadır. AB yakınsaması ölçülürken kredi iflas takası aralıklarının Polonya, Bulgaristan ve Türkiye için 2002’den 2009’a kadar analiz edilerek Almanya ile koentegrasyon ilişkisi oluşup oluşmadığına bakılmaktadır. Koentegrasyon ilişkisi Polonya için tespit edilmekte, Bulgaristan ile yapısal kırılmalı bir koentegrasyon bulunmakta ancak Türkiye için herhangi bir koentegrasyona rastlanmamaktadır. Bulgaristan için bulunan yapısal kırılma noktalarının AB giriş anlaşmasının imzalandığı tarih olan 2005 ve subprime krizinin başlangıcı olan 2007 olması önemli bulgular olarak göze çarpmaktadır. Ayrıca tezde subprime krizi sonrasında bu yakınsamanın bozulup bozulmadığı incelenmektedir. Son olarak Türkiye’nin kriz sonrası oluşan global koşullarda AB üyeliği perspektifi ve politika alternatifleri ele alımaktadır.

The first aim of this study is to analyze the impact securitization, an asset funding technique that involves the issuance of structured claims on the cash flow performance of a designated pool of underlying receivables, has had in funding the borrowings of Eastern European countries and their convergence to the EU. The empirical part of the thesis seeks to establish the relationship between EU convergence and its effect on credit default swap spreads, a type of credit derivative instrument used in synthetic securitizations. EU convergence is measured by using the CDS spreads of Poland, Bulgaria and Turkey from the mid-2002 to 2009 to search for a cointegration relationship between the spreads of each country and those of Germany. The cointegration relation is established in Poland, and with a structural break in the Bulgarian cases, but not in Turkey. A very important finding is that there are two possible structural breaks in the Bulgarian case, one coinciding with the signing of the Bulgarian accession treaty to the EU in 2005 and the other with the subprime crisis in end-2007. Then, the thesis concerns itself with the fallout from the subprime crisis and the consequent Eastern European credit crisis and seeks to establish whether the convergence trend has been broken. Finally, the policy aspects of this outcome regarding Turkey’s prospects for EU membership are discussed in light of the new global and EU situation following the subprime crisis.
Keywords: Avrupa Birliği_Bankacılık; Bankalar ve Bankacılık